Renal Dysplasia: A 6 Year Retrospective Study with Clinicopathological Correlation - Devadass, Clement Wilfred; Basavaraj, Madhu Aramane; Badila, Prasanna Shetty; Gouri, Mangala (Annals of Pathology and Laboratory Medicine, 2018)
Bakground: Renal dysplasia (RD) is rare congenital disease resulting from anomalous development of metanephric elements. The objective of the study was to evaluate the clinicopathologic features of RD with emphasis on the morphological changes. Methods: A retrospective study of RD cases diagnosed on nephrectomy specimens over a duration of six years at a south Indian tertiary health care centre. The clinical, radiological and macroscopic features were retrieved and microscopic morphological features were reviewed. Results: A total of 13 cases of RD were obtained, all of which were unilateral, with age range of 20 weeks of gestation to 54 years. Male predominance (61%) was noted and left kidney was preponderantly involved (69%). Associated genito-urinary tract anomalies were present in 54% of cases. Multicystic, hypodysplastic, hydronephrotic and segmental macroscopic types of RD were present in 39%, 23%, 23% and 15% of the cases respectively. The most consistent microscopic feature was primitive ducts surrounded by fibromuscular collarets. Conclusion: A diagnosis of RD should prompt the search of other associated urinary tract anomalies. Histopathologic examination is required for the definite diagnosis of RD and differentiation from other conditions like polycystic kidney disease, renal hypoplasia, renal atrophy and pure hydronephrosis. This differentiation is important from prognostic and genetic counselling point of view.